2015
DOI: 10.2142/biophysico.12.0_87
|View full text |Cite
|
Sign up to set email alerts
|

Rotational motion of rhodamine 6G tethered to actin through oligo(ethylene glycol) linkers studied by frequency-domain fluorescence anisotropy

Abstract: Investigation of the rotational motion of a fluorescent probe tethered to a protein helps to elucidate the local properties of the solvent and protein near the conjugation site of the probe. In this study, we have developed an instrument for frequency-domain fluorescence (FDF) anisotropy measurements, and studied how the local properties around a protein, actin, can be elucidated from the rotational motion of a dye tethered to actin. Rhodamine 6G (R6G) was attached to Cys-374 using newly-synthesized R6G-maleim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Prior to the D R analysis inside dextran droplets, we confirmed that the effect of polarization of the excitation light is negligible in the diffusion measurements from the almost identical translational correlation time, τ D , in the bulk with or without the use of polarizers (Table S1 and Section S1). In addition, the values of the lifetime of the fluorescence molecule τ L and of τ R in the bulk without dextran are almost identical with the reference values . Accordingly, we obtained τ D inside the dextran droplets and plotted the normalized diffusion coefficients, D / D bulk , against R for systems with and without polarizers (Figure a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the D R analysis inside dextran droplets, we confirmed that the effect of polarization of the excitation light is negligible in the diffusion measurements from the almost identical translational correlation time, τ D , in the bulk with or without the use of polarizers (Table S1 and Section S1). In addition, the values of the lifetime of the fluorescence molecule τ L and of τ R in the bulk without dextran are almost identical with the reference values . Accordingly, we obtained τ D inside the dextran droplets and plotted the normalized diffusion coefficients, D / D bulk , against R for systems with and without polarizers (Figure a).…”
mentioning
confidence: 99%
“…In addition, the values of the lifetime of the fluorescence molecule τ L and of τ R in the bulk without dextran are almost identical with the reference values. 32 Accordingly, we obtained τ D inside the dextran droplets and plotted the normalized diffusion coefficients, D / D bulk , against R for systems with and without polarizers ( Figure 2 a). We again observe a slow translational diffusion of R6G inside small dextran droplets with R < 20 μm, as in the case of TAMRA ( Figure 1 e).…”
mentioning
confidence: 99%